Tenofovir vaginal film as a potential MPT product against HIV-1 and HSV-2 acquisition: formulation development and preclinical assessment in non-human primates - Patel, Sravan Kumar; Agashe, Hrushikesh; Patton, Dorothy L.; Sweeney, Yvonne; Beamer, May A.; Hendrix, Craig W.; Hillier, Sharon L.; Rohan, Lisa C. (Frontiers in Reproductive Health, 2023)
Tenofovir (TFV) is an adenosine nucleotide analog with activity against HIV and HSV-2. Secondary analyses of clinical trials evaluating TFV gel as pre-exposure prophylaxis (PrEP) for HIV have shown that gel formulations of TFV provide significant protection against both HIV and HSV-2 acquisition in women who had evidence of use. An alternate quick-dissolving polymeric thin film, to deliver TFV (20 and 40 mg) has been developed as a potential multipurpose technology (MPT) platform. Film formulation was developed based on excipient compatibility, stability, and ability to incorporate TFV doses. Placebo, low dose (20 mg), and high dose (40 mg) films were utilized in these studies. The developed film platform efficiently incorporated high dose of TFV (40 mg/film), released more than 50% of drug in 15 min with no in vitro toxicity. Pharmacological activity was confirmed in an ex vivo HIV-1 challenge study, which showed a reduction in HIV-1 infection with TFV films. Films were stable at both doses for at least 2 years. These films were found to be safe in 2 This is a provisional file, not the final typeset article macaques with repeated exposure for 2 weeks as evidenced by minimal perturbation to tissues, microbiome, neutrophil influx, and pH. Macaque sized TFV film (11.2 mg) evaluated in a pigtail macaque model showed higher vaginal tissue concentrations of TFV and active TFV diphosphate compared to a 15 mg TFV loaded gel. These studies confirm that TFV films are stable, safe and efficiently deliver the drug in cervicovaginal compartments supporting their further clinical development.